Aplicação da escala SERVQUAL para a análise da qualidade dos serviços nas academias de musculação dos municípios de Angicos e Macau - Bezerra, Andrew Luiz Rodrigues (Universidade Federal Rural do Semi-Árido, 2019)
In response to the increase in physical inactivity and unhealthy lifestyle-related illnesses, the demand for health-promoting activities has steadily increased over the past few years. Among the sports that report the highest adhesions is the bodybuilding, which aims to develop the body and promote health in general through resistive movements using weights. However, only the pursuit of better health does not guarantee organizations lifelong or unconditional customer loyalty, and companies need to analyze their performance through the perception of quality from the customer's perspective about the service they offer. . The present work analyzed the quality of the services of the weight training academies of the municipalities of Angicos / RN and Macau / RN through the SERVQUAL methodology, validating the research data using Cronbach's alpha, which did not present values below 0.67, and identifying averages, medians and deviations for the items, then subdivided into the five dimensions of service quality, identifying the numerical differences (Gaps) between the expectations and perceptions of customers regarding the service provided by gyms, having dimensional performance (Gap) Reliability (-1.32), Security (-1.09), Empathy (-0.92) and Responsiveness (-0.85), highlighting the main items that contributed to the negative performance of all dimensions. Analyzing the performance of each dimension in a general analysis, similar analyzes were developed for the municipalities covered in the research, as well as assembling the customer profile and verifying the statistical similarity of the municipalities' performance through the Student's t-test. negative, which was reflected in the final impossibility in the development of the linear regression model for the research data. At the end of the work, improvements based on Quartis prioritization were proposed for the highest expectations, lowest perceptions and highest identified critical Gaps so that once identified they can be mitigated.
Monografia
Keywords: Qualidade; Serviços; Expectativa; Percepção; SERVQUAL; Quality; Services; Expectancy; Perception; SERVQUAL; ENGENHARIAS::ENGENHARIA DE PRODUCAO